TEACHER’S INTERPERSONAL COMMUNICATION AND ITS IMPACTS ON STUDENTS’ MOTIVATION IN EFL LEARNING - Aqzhariady Khartha; Sultan Baa; Chairil Anwar Korompot (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This research attempted to reveal the types of interpersonal communication used by an English teacher in the teaching and learning process, the factors that influence it, and its impacts on students’ motivation in EFL learning at SMPN 10 Makassar. To analyze the data for this research, a descriptive qualitative method was used. The English teacher and 5 students who were involved in Zoom meetings were taken as the subject of this research. The data was gained from classroom observation and interviews. This research found that there were 15 types of verbal and 6 types of non-verbal interpersonal communication used by the teacher during the lesson. This research also found the factors that can support interpersonal communication between teachers and students. Those factors include understanding, closeness, good feedback, affection, empathy, equality, ethic, positiveness, supportiveness, openness between teachers and students; and adequate virtual communication media. On the flip side, the factors that can inhibit the effectiveness of interpersonal communication include there is no understanding, openness, affection, and respect between teachers and students; and the other factors come from passive communicants (students), inadequate virtual communication media, and noise generated during the teaching-learning process. The result of the findings also showed that there were positive and negative impacts that students felt from the teacher's interpersonal communication on their motivation to learn English